Planning and Analysis of the Implementation of the Merdeka Curriculum: (A Case Study at SMK Roudlotul Huda Padangratu) - Fahmy Singgih; Heri Saputra; Rohani Awan Ahmad; Pratama Avriyansyah; Sri Andayani (LP3M KH Yazid Karimullah Institute, 2026)
This study aims to analyze the planning, implementation, and supporting and inhibiting factors of the Merdeka Curriculum in the context of vocational education. This research employs a qualitative approach using a case study method at SMK Roudlotul Huda Padangratu. Data were collected through interviews, observations, and documentation, and analyzed using the interactive model of Miles and Huberman as well as a policy analysis framework. The results show that the planning of the Merdeka Curriculum has been carried out through the development of the School Operational Curriculum (KOSP), teaching modules, and teacher training programs. The implementation indicates changes in project-based learning, differentiated instruction, and the strengthening of vocational competencies. However, challenges remain, including limited teacher understanding, inadequate facilities, and suboptimal policy communication. This study concludes that the success of the Merdeka Curriculum implementation is highly dependent on human resource readiness, institutional support, and the effectiveness of education policies at the local level